Modification of Blood Test Draw Order to Reduce Blood Culture Contamination: A Randomized Clinical Trial. (1st October 2019) - Zimmerman, Frederic S; Karameh, Hani; Ben-Chetrit, Eli; Zalut, Todd; Assous, Marc; Levin, Phillip D
Abstract: Background: Blood culture contamination leads to unnecessary interventions and costs. It may be caused by bacteria in deep skin structures unsusceptible to surface decontamination. This study was designed to test whether diversion of blood obtained at venipuncture into a lithium heparin tube prior to aspiration of blood culture reduces contamination. Methods: The order of blood draws for biochemistry and blood cultures was randomized. Following standard disinfection and venipuncture, blood was either aspirated into a sterile lithium heparin tube before blood culture bottles (diversion group) or blood cultures first and then lithium heparin tube (control group). All study personnel were blinded with the exception of the phlebotomist. Results: After exclusions, 970 blood culture/biochemistry sets were analyzed. Contamination occurred in 24 of 480 (5.0%) control vs 10 of 490 (2.0%) diversion group cultures ( P = .01). True pathogens were identified in 26 of 480 (5.4%) control vs 18 of 490 (3.7%) diversion cultures ( P = .22). Despite randomization, demographic differences were apparent between the 2 groups. A post hoc analysis of 637 cultures from 610 medical patients admitted from home neutralized demographic differences. Culture contamination remained more frequent in the control vs diversion group (17/312 [5%] vs 7/325 [2%]; P = .03). Fewer diversion group patients were admitted to hospital (control: 200/299 [66.9%] vs diversion: 182/311 [58.5%]; P = .03), and length of stay was shorter (control: 30 hours [interquartile range IQR, 6–122] vs diversion: 22 [IQR, 5–97]; P = .02). Conclusions: Use of lithium heparin tubes for diversion prior to obtaining blood cultures led to a 60% decrease in contamination. This technique is easy and inexpensive and might decrease overall hospital length of stay. Clinical Trials Registration: NCT03966534. Abstract : In this randomized trial, blood was aspirated into a sterile lithium heparin tube either before (diversion) or after (control) obtaining blood cultures. Diversion reduced blood culture contamination by 60%. This technique does not waste blood and is easy and effective.